2019
DOI: 10.1142/s021759081741003x
|View full text |Cite
|
Sign up to set email alerts
|

Does Media Attention Affect Firms’ Environmental Protection Efforts? Evidence From China

Abstract: Using data from publicly traded firms in China, we examine the relationship between media attention and firms’ environmental protection efforts. We show that: (1) media attention induces firms to exert more effort in environmental protection, (2) state-owned firms are more responsive to media attention than non-state-owned firms regarding environmental protection and (3) firms are more responsive when faced with local media attention and negative media reports. The results are robust to the subsample of heavil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Using samples of environmentally sensitive industries, Zhou et al (2022) confirmed that increased community pressure is negatively associated with corporate pollution levels, and thus, positively associated with corporate environmental performance. Kong et al (2020) reviewed the literature and pointed out that media attention induces firms to exert more effort on environmental protection, especially when there are adverse media reports. Xue et al (2021) empirically found that both media attention and government regulation were significantly positively correlated with environmental information disclosure; notably, the more adverse the effect of government regulation, the more media attention promotes environmental information disclosure.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Using samples of environmentally sensitive industries, Zhou et al (2022) confirmed that increased community pressure is negatively associated with corporate pollution levels, and thus, positively associated with corporate environmental performance. Kong et al (2020) reviewed the literature and pointed out that media attention induces firms to exert more effort on environmental protection, especially when there are adverse media reports. Xue et al (2021) empirically found that both media attention and government regulation were significantly positively correlated with environmental information disclosure; notably, the more adverse the effect of government regulation, the more media attention promotes environmental information disclosure.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…The media has paid more attention to corporate environmental behavior since the new law. As an effective tool of public scrutiny, media can reduce the information asymmetry between companies and the public, and play the auxiliary function on environmental regulation (Kong et al, 2020). Indeed, Company A quickly corrected its improper environmental behavior after perceiving the negative impact of negative news.…”
Section: Discussionmentioning
confidence: 99%
“…Media coverage and promotion of environmental responsibility reinforce public awareness of environmental protection and behavioral response motives, resulting in different economic rewards for firms with different corporate environmental responsibility performances (Kong et al, 2019). Enterprises with greater media attention have higher visibility, which can improve the awareness of environmental protection and enhance the value of enterprises (Wu et al, 2020).…”
Section: The Moderating Effect Of Media Attentionmentioning
confidence: 99%
“…To support hypotheses three to six and the moderating effect of media attention on the relationship between environmental protection and corporate sustainable development ability, we constructed models (Eqs. [3][4][5][6].…”
Section: The Model Designmentioning
confidence: 99%